2012
DOI: 10.1007/s00339-012-6875-9
|View full text |Cite
|
Sign up to set email alerts
|

Improvement on HVOF sprayed Diamalloy coatings by laser irradiation

Abstract: We investigated the structure change, surface properties (roughness, porosity, and hardness), tribological, and electrochemical performances of HVOF sprayed Ni20Cr-10W-9Mo-4Cu-1C-1B-1Fe (Diamalloy-4006) coatings before and after laser irradiation. The results showed that the friction and wear resistance of the coatings were improved significantly with an optimized laser irradiation process. The improvement can be attributed to the improved roughness and hardness, as well as the formation of oxides Cu x O and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In addition, the high melting point of elements such as W and Mo might also produce high hardness oxides, carbides, and borides at elevated temperature, which can improve both mechanical properties and wear resistance of the coating [27][28][29]. At present, it had been found that NiCrWMoCuCBFe coating possesses excellent mechanical properties, corrosion resistance, and cavitation erosion resistance [30][31][32][33]. However, there were few studies on its tribological properties at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the high melting point of elements such as W and Mo might also produce high hardness oxides, carbides, and borides at elevated temperature, which can improve both mechanical properties and wear resistance of the coating [27][28][29]. At present, it had been found that NiCrWMoCuCBFe coating possesses excellent mechanical properties, corrosion resistance, and cavitation erosion resistance [30][31][32][33]. However, there were few studies on its tribological properties at high temperature.…”
Section: Introductionmentioning
confidence: 99%